Erioflorin and Erioflorin Acetate Induce Cell Death in Advanced Prostate Cancer Through ROS Increase and NF-κB Inhibition - Cecilia Villegas; Iván González-Chavarría; Viviana Burgos; Jaime R. Cabrera-Pardo; Bernd Schmidt; Cristian Paz (Journal of Xenobiotics)
Germacranes are a type of sesquiterpene lactones with anti-inflammatory and cytotoxic properties against cancer cell lines. In this in vitro study, erioflorin and erioflorin acetate were isolated and purified from the leaves of Podanthus mitiqui Lindl (Mitique or Mitriu), a shrub endemic to Chile and traditionally used in Mapuche medicine to treat urinary and digestive disorders. Their effects on advanced prostate cancer cell lines (DU-145 and 22Rv1) were evaluated. Cytotoxicity was assessed using real-time cell death and clonogenic assays. Apoptosis was determined by measuring reactive oxygen species (ROS), mitochondrial membrane potential (ΔΨm), and apoptotic cell percentage through flow cytometry. Gene expression of BAX and BCL-2 was analyzed via RT-qPCR, while NF-κB activation was studied in DU-145 cells and human monocytic NF-κB reporter assays using LPS stimulation and alkaline phosphatase activity quantification. Erioflorin acetate exhibited the highest cytotoxicity, with IC50 values of 35.1 µM (22Rv1) and 27.3 µM (DU-145), compared to erioflorin, which had IC50 values of 50.3 µM and 56.5 µM, respectively. Both compounds increased ROS levels, reduced ΔΨm, and induced apoptosis. RT-qPCR analysis revealed that erioflorin elevated the BAX/BCL-2 ratio, and both compounds inhibited NF-κB activation by preventing IκBα phosphorylation. In conclusion, the findings demonstrate that erioflorin and erioflorin acetate exert significant in vitro cytotoxic and cytostatic effects on prostate cancer cells, supporting their potential as natural candidates for prostate cancer therapy.